The Design of Baby Equipment Rental Website Using Laravel Framework at Rafana Rent Store - Sitti Nurhaliza; Isdayani B; Rahmat Siswanto (Brilliance: Research of Artificial Intelligence, 2025)
Technological developments have encouraged various business sectors to adapt to digitalization, including the baby equipment rental sector. This study aims to design and build a web-based baby equipment rental information system using the Laravel Framework at the Rafana Rent Store in Palopo City. The method used is a qualitative descriptive approach using a prototype development model. Data was obtained through interviews, observations, and documentation of the rental process carried out manually. The results of this study indicate that the system created can overcome various problems in the manual rental process, such as delays in service, recording, which is still done manually in notebooks, and lack of efficiency in payment confirmation. This system provides main features such as online ordering, uploading proof of payment, and managing stock of goods. Through the trials, the system was considered to facilitate customers in carrying out the rental process, which can be done anytime and anywhere, and help shop owners manage transaction data more accurately and provide efficient service to customers. Implementing this system is expected to improve the quality of service and speed up and simplify the rental process. The Rafana Rent Store can manage its business more professionally and be ready to face the digitalization era. This system can also be an example of the application of information technology in micro businesses.